Calvinism a very short introduction - Balserak, Jon 1964- (Very short introductions, 2016)
In this work Jon Balserak explores major ideas and issues associated with the Calvinist system of thought. He looks at how Calvinist ideas and practices spread and took root, helping shape societies today. Much of contemporary thought - especially Western thought - on everything from civil government to money, suicide, and divorce has been influenced by Calvinism. Balserak also combats common misconceptions about Calvinism, and explores the relationship between Calvinism and the modern world